Two protons masquerading as a metal ion? Anionic coordination polymers of uranyl ion and tetrahydrofurantetracarboxylate with protonated or metal-complexed azamacrocyclic cations. Issue 1 (2nd January 2023) - Thuéry, Pierre; Harrowfield, Jack
Abstract: Two complexes, [ R, S -Me6 cyclamH2 ][(UO2 )3 (thftc)2 ] (1 ) and [(UO2 )3 (thftc)2 Cu( R, S -Me6 cyclam)]⋅2H2 O (2 ), have been obtained from reaction of uranyl nitrate with (2 R*, 3 R*, 4 S*, 5 S* )-tetrahydrofurantetracarboxylic acid (H4 thftc) under solvo-hydrothermal conditions in the presence of either R, S -Me6 cyclam⋅4HNO3 or [Cu( R, S -Me6 cyclam)(NO3 )2 ] ( R, S -Me6 cyclam = 7( R ), 14( S )-5, 5, 7, 12, 12, 14-hexamethyl-1, 4, 8, 11-tetraazacyclotetradecane). Isomerization in situ results in both complexes involving the chiral 2 R*, 3 R*, 4 R*, 5 S* form of the ligand. (UO2 )3 (thftc)2 2– diperiodic networks with the V2 O5 topology are formed in both cases, which are separated by layers of hydrogen bonded counterions in 1, or united into a triperiodic framework of 3, 5T1 topology by bridging copper(II) cations in 2 . The packing of anionic sheets and azamacrocyclic moieties is however nearly identical in the two species, as a consequence of the similar stereochemistry of the otherwise different interactions linking the diperiodic polymer units. GRAPHICAL ABSTRACT: UF0001